Validity and reliability of the German multidimensional fatigue inventory in spinal muscular atrophy. Issue 3 (22nd February 2022) - Binz, Camilla; Osmanovic, Alma; Thomas, Nele H.; Stolte, Benjamin; Freigang, Maren; Cordts, Isabell; Griep, Ramona; Uzelac, Zeljko; Wurster, Claudia D.; Kamm, Christoph; Siegler, Hannah A.; Wieselmann, Gary; et al.
Abstract: Objective: Fatigue is a common and burdensome symptom of spinal muscular atrophy. Given its complex interactions, different dimensions of fatigue need to be investigated. The Multidimensional Fatigue Inventory is a widely used instrument that captures five distinct dimensions. The aim of this study was to investigate the validity and reliability of the German Multidimensional Fatigue Inventory in spinal muscular atrophy and to evaluate the presence of clinically relevant fatigue. Methods: One hundred and forty adult spinal muscular atrophy patients completed the Multidimensional Fatigue Inventory in a nationwide, multicenter, cross‐sectional study. Structural validity was explored using principal component analysis. Cronbach's α was calculated to evaluate internal consistency. Convergent validity was assessed by correlation with a Visual Analog Scale for fatigue and the EuroQol‐Five Dimension‐Five Level Scale as a measure of quality of life. Results: The original five‐component model of the questionnaire constituted an acceptable fit. Internal consistency and convergent validity of general, physical, mental fatigue, and reduced activity were good. We observed a floor effect for mental fatigue . While physical fatigue exceeded the cutoff for clinically relevant fatigue, all dimensions but reduced motivation correlated negatively with quality of life. Age, depression, and ≥4 copies of the survival motor neuron 2 gene were associated with higher general/physical fatigue ; unemployed participants reported higher scores for reduced activity/motivation . Interpretation: The Multidimensional Fatigue Inventory is a valid and reliable instrument to assess different dimensions of fatigue in spinal muscular atrophy. Fatigue is a relevant problem in spinal muscular atrophy and its assessment should be incorporated into standard care.